Hungarian Presence in Romanian Danube Ports (1895 – 1929): “Royal Hungarian River Navigation Society” - Ionel Constantin MITEA (ACROSS)
The end of the 19th century found the Danube navigation in a full process of diversification of river operators, who fiercely disputed their economic interest, among them, the Hungarian company Magyar Folyam és Tengerhajózási Részvénytársaság – MFTR. Founded in 1895, based on an initiative of the Hungarian government, the company had a substantial presence in Romanian ports, marked by several historical moments, highlighted in this study. MFTR registered an active presence in almost all Romanian ports and was a part of the emerging landscape of the economic development of the Danube area. As it had to be, the competitive “spirit” present in the environment of the river navigation companies that operated the Romanian ports during the reference period and their need to promote and protect their interests as best as possible, generated a series of disputes with the Romanian authorities. Knowing the nature of the relations between Romania and Hungary from the years before the First World War, there were moments when MFTR highlighted the combination of “political-economic rivalry” existing between the Hungarian and Romanian authorities, the company’s representatives distorting the realities in our country.